Haute-à-Porter / Filep Motwary. - Motwary, Filep (Modemuseum Hasselt, 2016)
Haute couture often dazzles us with its precision, craftsmanship and the extravaganza inherent in it. Clothing items are made out of proportion; unique materials are used and everything is hand-finished. But, the prêt-à-porter collections of today comply with the classic principles of haute couture. The items shown on the catwalk should theoretically be wearable, but often in reality this is not entirely the case. Haute-à-Porter examines the relationship between Haute Couture and prêt-à-porter collections and shows the evolution in their relationship over the past 25 years.